Diffusion tensor imaging of the median nerve: intra-, inter-reader agreement, and agreement between two software packages. - Guggenberger R; Nanz D; Puippe G; Rufibach K; White LM; Sussman MS; Andreisek G; Guggenberger, Roman; Nanz, Daniel; Puippe, Gilbert; Rufibach, Kaspar; White, Lawrence M; et al. (Skeletal Radiology, 2012)
Objective: To assess intra-, inter-reader agreement, and the agreement between two software packages for magnetic resonance diffusion tensor imaging (DTI) measurements of the median nerve.Materials and Methods: Fifteen healthy volunteers (seven men, eight women; mean age, 31.2 years) underwent DTI of both wrists at 1.5 T. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) of the median nerve were measured by three readers using two commonly used software packages. Measurements were repeated by two readers after 6 weeks. Intraclass correlation coefficients (ICC) and Bland-Altman analysis were used for statistical analysis.Results: ICCs for intra-reader agreement ranged from 0.87 to 0.99, for inter-reader agreement from 0.62 to 0.83, and between the two software packages from 0.63 to 0.82. Bland-Altman analysis showed no differences for intra- and inter-reader agreement and agreement between software packages.Conclusion: The intra-, inter-reader, and agreement between software packages for DTI measurements of the median nerve were moderate to substantial suggesting that user- and software-dependent factors contribute little to variance in DTI measurements.